The Activity of Antioxidant and Anaerobic Glycolysis Enzymes Under Thermal Gradient Exposure in Palearctic Species Lymnaea stagnalis - Vereshchagina К.P.; Lubyaga J.А.; Gurkov А.N.; Shchapova Е.P.; Madyarova E.V.; Kondrat’eva Е.М.; Golubev А.P.; Timofeyev М.А.; Aksenov-Gribanov D.V. (Journal of Stress Physiology & Biochemistry, 2013)
The aim of present study was the evaluation of antioxidant (peroxidase, catalase, glutathione S transferase) and anaerobic glycolysis (lactate dehydrogenase) enzymes activity under thermal gradient in Palearctic species Lymnaea stagnalis (Linnaeus, 1758). Activity of peroxidase, lactate dehydrogenase and glutathione S-transferase elevated in L. stagnalis under thermal exposure. Opposite to this, activity of catalase decreased in same condition. We demonstrated antioxidant nd anaerobic glycolysis enzymes participation in adaptation mechanisms to environmental hanges in gastropods L. stagnalis.